2004
DOI: 10.1038/sj.npp.1300592
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of a Major QTL Influencing Oral Morphine Intake in C57 and DBA Mice Using Reciprocal Congenic Strains

Abstract: C57BL/6 (B6) and DBA/2 (D2) mice exhibit disparate behavior when tested for voluntary morphine intake in a two-bottle choice drinking paradigm with B6 mice consuming 10 times more drug than D2 mice. Previous genetic mapping studies identified a locus, Mop2, on the proximal part of chromosome 10 that explained over half of the genetic variance in this mouse model of opioid selfadministration. We constructed a set of reciprocal congenic strains between B6 and D2 mice in which the proximal portion of chromosome 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(71 citation statements)
references
References 17 publications
2
67
1
1
Order By: Relevance
“…The Chr. 10 'Morphine-preference' (Mop) QTL was replicated (Alexander et al, 1996) and has been confirmed in reciprocal congenic mouse strains (Ferraro et al, 2005).…”
Section: Introductionmentioning
confidence: 91%
“…The Chr. 10 'Morphine-preference' (Mop) QTL was replicated (Alexander et al, 1996) and has been confirmed in reciprocal congenic mouse strains (Ferraro et al, 2005).…”
Section: Introductionmentioning
confidence: 91%
“…In rodents, genes that are implicated by QTL studies include the µ-opioid receptor 1 (OPRM1) in morphine preference 118,119 , the multiple PDZ-binding domain protein (MPDZ) in acute pentobarbital and ethanol withdrawal 120 , NPY in ethanol preference 121 , glutamic acid decarboxylase (GAD1), a GABA biosynthetic enzyme, in ethanol-induced locomotion 122 , and DRD2 and HTR1B in ethanol preference 31 . The functional allele has not been verified in any of these cases, but in other examples, effects of alleles, including artificial gene knockouts, are directly known.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these phenotypes have now been studied in "quantitative trait locus" paradigms. In these approaches, recombinant inbred (RI) mice are frequently studied [49,50]. Each strain of these RI mice contains a different complement of reassorted chromosomal segments derived from two progenitor inbred strains.…”
Section: B Studies Of Murine Strain Differences In Drug Related Phenmentioning
confidence: 99%